A study of football goal trajectories of trained players through a kinetic model - Ming Zi; Dan Gao (The Journal of Engineering, 2023)
Abstract Training on shooting technique can effectively improve the score in football games. This paper constructed a kinetic model of the football during its flight based on the Newton's second law after analyzing the force during flying and proposed to solve the model with numerical simulation before drawing the simulation trajectories of a flying football. The results showed that the kinetic model effectively simulated the flight trajectory of the football. The further the distance of the shot was, the lower the average hit rate of the football was, and the more the football flight trajectory deviated from the reference trajectory; however, after the training assisted by the kinetic model, not only the average hit rate was improved, but also the average deviation of the flight trajectory was reduced.